Barriers to Scientific Creativity of Physics Teacher in Practicing Creative Product Design. (March 2020) - Suyidno, S; Susilowati, E; Arifuddin, M; Sunarti, T; Siswanto, J; Rohman, A
Abstract: Barriers to scientific creativity often make it difficult for physics teachers to recognize their creative potential, let alone train their students to be creative. The research aims to identify the physics teachers' ability in practicing creative product design and their creative barriers. This research includes mix-methods using a survey approach and continued by Focus Group Discussion. It has involved 67 physics teachers in South Kalimantan divided into three groups (senior teachers, beginner teachers, pre-service teachers). The teacher's answers are analyzed by descriptive qualitative. The results showed that teachers' ability to design creative products limited to creative ideas and scientists; but it has non-integrated mathematical reasoning and technical design in designing an applicable product. The teacher's negative belief in scientific creativity and their learning are the main factors of creating barriers. Other factors are limited study time, laboratory equipment, teaching materials, and the amount of material structure.